Strategic Plan Perception Scale; A Scale Development Study - AYDIN, Eray; KARAKULLE, İsmail; POLAT, Hakkı (Dumlupinar University Journal of Social Sciences, 2022)
This study provides a scale development with two sub dimensional for public institution employees to determine the employees' perceptions regarding the preparation, implementation, and evaluation of the strategic plan. In this study, a 21-item scale has been developed in three phases. In the first part, the scope of the scale has been defined, and the literature was reviewed in this context. Thoughts of experts in the field have been received then in the second step, an item pool for scale has been created. In the third stage, the final version of the scale was prepared by taking into account the grammar rules. The scale has been applied to employees working basically in public institutions and universities involved in the preparation or implementation processes of the strategic planning. The sample size has been determined as 216 employees according to the random sample method besides Cronbach's alpha coefficient has been calculated for reliability. Exploratory Factor Analysis and Confirmatory Factor Analysis have been applied for the validity test. Bartlett and Kaiser-Meyer-Olkin (KMO) tests have been used for sampling adequacy. The fit indices calculated in the confirmatory factor analysis were; RMSEA: 0.070, χ2: 1.846, SRMR: 0.039, NFI: 0.97, GFI: 0.85, CFI: 0.99. The findings have been shown that scale validity was achieved. Likewise, the reliability test result has been shown that the scale was two-dimensional and Cronbach's alpha coefficient was 0.97.
Keywords: Strategic Planning; Ölçek Geliştirme; Scale Development; Strategic Management; Strategic Planning; Scale Development; Stratejik Yönetim; Stratejik Yönetim; Stratejik Planlama; Ölçek Geliştirme; Stratejik Planlama; Strategic Management; 4. Education